(untitled) (Training and Practice : Journal of Educational Sciences, 2018)
Although national wealth of economies significantly increased after the Second World War, feelings of happiness hardly changed. In terms of differentiating between financial and subjective well-being, happiness research provides scientific answers. I am examining the different paths to happiness through the lens of the various views of empirical research on happiness, positive psychology and the Buddhist economics in my thesis. On the basis of my research among high school students, I am analysing if students’ personal characteristics or the external environmental effects lead to happiness. Pessimism, materialism and the optimizing personality types support them or stop them from achieving subjective well-being. Although young people should find sources of happiness on their own, we can help them by introducing a high school education boosting students’ positive attitude.